Adenocarcinoma developing from gastric heterotopic pancreas: a case report and short review - Qi, Ran; Li, Kun; Shi, Baomin (Frontiers in Surgery, 2024)
Heterotopic pancreas is a relatively rare condition that may be associated to clinical complaints or signs. Here, we report a case of gastric heterotopic pancreas assictaed to ductal adenocarcinoma. Obstructive jaundice was the initial symptom prompting medical intervention. A 73-year-old male patient presented with yellow staining of the skin and sclera, and dull epigastric pain. Contrastenhanced computed tomography showed stenosis of the extrahepatic distal bile duct and mass lesions of the antrum. The patient underwent tumor resection, distal gastrectomy (Billroth II), and common bile duct exploration. Postoperative pathological examination revealed an adenocarcinoma located in the wall of the gastric antrum. Immunohistochemical results suggested that the tumor originated from the pancreas. Heterologous pancreatic tissue and a dilated pancreatic duct were found in the tumor. These findings suggest malignant transformation of the gastric heterotopic pancreas. Of note, jaundice as clinical complaint for adenocarcinoma associated to gastric heterotopic pancreas.